Young criminal lives : life courses and life chances from 1850 - Godfrey, Barry S.; Cox, Pamela, 1970-; Shore, Heather, 1964-; Alker, Zoe (Oxford : Oxford University Press, 2017)
This work uses innovative digital methods to track the life course of 500 Victorian children living within, or at the margins of, the early English juvenile reformatory system, offering rich interdisciplinary insights into how far the efforts of these institutions were successful, and their long-term, practical impact.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 8, 2017).
Keywords: Juvenile delinquency -- Great Britain -- History -- 19th century; Juvenile justice, Administration of -- Great Britain -- History -- 19th century; True Crime; Social services & welfare, criminology